Turkish Journal of Urology 2022
DOI: 10.5152/tud.2022.22014
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron as a Medical Expulsive Therapy for 5-10 mm Distal Ureteral Stones: A Prospective, Randomized, Comparative Study

Abstract: Objective: The aim of this study was to assess the efficacy and safety of mirabegron as a medical expulsive therapy in patients with distal ureteral stones of 5-10 mm size. Material and methods: A prospective, comparative study included 96 patients with radiopaque distal ureteral stones of 5-10 mm who were randomly allocated and treated by medical expulsive therapy in 2 groups from January 2019 to December 2020. Patients in group A received only ketorolac 30 mg/day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Study characteristics are summarized in Table 1 , comprising 701 participants. All studies were RCTs ( Bayar et al, 2020 ; Abdel-Basir Sayed et al, 2022 ; Mayer, 2022 ; Morsy et al, 2022 ; Rajpar et al, 2022 ; EAU, 2023 ; Samir et al, 2023 ), which had accrued between September 2009 and November 2022 ( Figure 1 ). These studies were conducted in the United States, Pakistan, Turkey, Egypt, China, and Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are summarized in Table 1 , comprising 701 participants. All studies were RCTs ( Bayar et al, 2020 ; Abdel-Basir Sayed et al, 2022 ; Mayer, 2022 ; Morsy et al, 2022 ; Rajpar et al, 2022 ; EAU, 2023 ; Samir et al, 2023 ), which had accrued between September 2009 and November 2022 ( Figure 1 ). These studies were conducted in the United States, Pakistan, Turkey, Egypt, China, and Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…For ureteral stones <10 mm, 68% of patients in group A expelled the stone during therapy, compared to 60% and 20% in groups B and C, respectively ( Morsy et al, 2022 ). Furthermore, based on the data on Tang et al, in patients with 5-mm stones, the experimental group (mirabegron 50 mg once daily plus tamsulosin 0.2 mg once daily) had a higher SER than the control group (tamsulosin 0.2 mg once daily) ( Abdel-Basir Sayed et al, 2022 ). Although mirabegron appears to demonstrate a similar or even superior stone expulsion effect compared to tamsulosin, further large-scale RCTs are essential to substantiate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…4B). Three trials reported analgesic consumption in the articles which showed less analgesic consumption in the mirabegron group [10,11,15]. But we could not conduct an overall quantitative analysis of the amount of analgesic consumption due to different types of analgesics used in each study.…”
Section: The Expulsion Rate Of Mirabegron For Stonesmentioning
confidence: 95%
“…The search strategy identi ed 456 articles and 6 trials [10][11][12][13][14][15] (including 5 RCTs) with 462 patients were included in the nal analysis. The literature screening process is shown in Fig.…”
Section: Study Selection and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation